Isu Keberlanjutan dan Persaingan Usaha: Kapan Otoritas Harus Campur Tangan? - Riris Munadiya (Jurnal Persaingan Usaha, 2022)
Abstract The issue of sustainable development has been a priority for the government and the world since the last few years. It is anticipated that Indonesia will achieve net zero emission by 2060. This big ambition is considered to require large funds, and business actors and the government are competing at different tempos. This acceleration needs to be balanced with the supervision of competition so that the process does not lead to a more concentrated market by large business actors who incidentally have the ability to achieve sustainable products. Supervision by this authority should be done at this time. On the other hand, competition law needs to take the right position so as not to create obstacles to the achievement of sustainable development goals.